Joint modelling of correlated binary outcomes regarding the misconceptions of HIV transmission: a study with reference to the tertiary and vocational education trainees in Sri Lanka - Samarakoon, Thilini; Withanage, Niroshan; Samarakoon, Nimalakith; Lekamge, Upul; Silva, Nadesha De (International Journal Of Community Medicine And Public Health, 2020)
Background: Currently, people infected with HIV are largely discriminated and discredited. Misunderstanding about the mechanism of HIV transmission has been identified as one reason for discrimination. This study assessed the socio-demographic and behavioral risk factors of the two misconceptions about HIV transmission, namely HIV is transmitted by sharing cups and plates with an HIV infected person (Myth 1) and HIV is transmitted by mosquito bites (Myth 2) among the trainees who were selected to the Tertiary and Vocational Education Training (TVET) Centers in Sri Lanka. Methods: This study applied stratified random sampling to select 955 respondents. A self-administered structured questionnaire was used to collect the data. Generalized linear mixed model (GLMM) approach was applied to find the associations between misconceptions about HIV and socio-demographic and behavioral risk factors of the trainees. Results: Level of education of trainees, family relationship, knowledge on sexual and reproductive health (SRH), knowledge about the risk of getting HIV after sexual intercourse, whether the trainee had participated in seminar or workshop on sexually transmitted diseases were identified as the possible factors to detect the knowledge about the misconceptions of HIV transmission. Conclusions: Even though the level of education among different social segments have not revealed remarkable differences in knowledge, the study convinced that the youth should be provided better awareness and education on STD and HIV through countrywide workshops and awareness programmes.